Effect of titanium dioxide (Tio2) nanoparticles on the wear rate of marine journal bearings made of composite materials - Suadad Noori Ghani; Ali Sadiq Alithari; Hala Salman Hasan (Results in Engineering, 2025)
In marine applications, journal bearings are vital components that face wear and friction challenges under harsh operating conditions. In this research, composite materials based on epoxy resin reinforced with chopped glass and carbon fibers, supplemented with titanium dioxide (TiO₂) nanoparticles at weight percentages (1 %, 1.5 %, and 2 %), were developed. Sixteen composite samples were prepared and tested according to ASTM standards to evaluate performance under loads of 10 and 15 N. Results showed that the best performance was achieved when 1.5 % Tio₂ was added with 4 % glass fibers and 4 % carbon fibers, with wear rates reduced by 54.4 % and 57.45 %, and friction coefficient improved by 65 % ​​and 64.8 % at loads of 10 and 15 N, respectively. In contrast, increasing the Tio₂ concentration to 2 % resulted in performance degradation due to particle agglomeration. To support the results, a statistical regression analysis was conducted, revealing a strong and significant relationship between the variables. The coefficient of determination (R²) was 0.974, indicating that the model explained 97.4 % of the variance in the data. A scanning electron microscope (SEM) was also used to analyze the microstructure and particle distribution, and the images confirmed the optimal homogeneity of the sample and the effectiveness of the fiber and nanoparticle distribution in enhancing performance.